2021
DOI: 10.1016/j.cjco.2020.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Ten Questions Cardiologists Should Be Able to Answer About Cardiac Sarcoidosis: Case-Based Approach and Contemporary Review

Abstract: Sarcoidosis is an inflammatory multisystemic disease of unknown etiology characterized by the formation of noncaseating epithelioid cell granulomas. Cardiac sarcoidosis might be life-threatening and its diagnosis and treatment remain a challenge nowadays. The aim of this review is to provide an updated overview of cardiac sarcoidosis and, through 10 practical clinical questions and real-life challenging case scenarios, summarize the main clinical presentation, diagnostic criteria, imaging findings, and contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 130 publications
0
15
0
1
Order By: Relevance
“… 9 Cardiac involvement in sarcoidosis has been reported in as many as 27% of autopsy studies in some North American cohorts, but many cases may be undiagnosed. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Cardiac involvement in sarcoidosis has been reported in as many as 27% of autopsy studies in some North American cohorts, but many cases may be undiagnosed. 10 …”
Section: Discussionmentioning
confidence: 99%
“…CMR is better at detecting the chronic fibrotic stage of CS and has a good prognostic role with late gadolinium enhancement (LGE) quantification usually present in the subepicardium and midmyocardium [18]. Indeed, multiple studies have shown an association between LGE and increased mortality and ventricular arrhythmias [1 ▪ ,19]. On the other hand, PET/CT performs better at detecting the active inflammatory stage of CS and is a good tool for the follow-up after initiation of IT [1 ▪ ].…”
Section: Cardiac Magnetic Resonance and Hybrid Imagingmentioning
confidence: 99%
“…Indeed, multiple studies have shown an association between LGE and increased mortality and ventricular arrhythmias [1 ▪ ,19]. On the other hand, PET/CT performs better at detecting the active inflammatory stage of CS and is a good tool for the follow-up after initiation of IT [1 ▪ ].…”
Section: Cardiac Magnetic Resonance and Hybrid Imagingmentioning
confidence: 99%
See 2 more Smart Citations